Tinjauan Potensi dan Pemanfaatan Energi Panas Bumi di Pulau Flores - Richardo Barry Astro (Postgraduate, University of Mataram, 2023)
Geothermal energy on Flores Island is a suitable subject for a contextual approach in physics studies. Research activities, exploration, and the practical application of geothermal energy rely on fundamental physical concepts and principles. Flores Island and the surrounding archipelago are endowed with significant geothermal potential. Consequently, this research endeavor, aimed at assessing the potential and utilization of geothermal energy on Flores Island, serves as an excellent resource for contextual physics learning, particularly in the context of Flores Island. This research uses a literature study approach by reviewing related literature to obtain information about the research object. Flores Island and its neighboring island groups host 24 volcanoes. Specifically, Flores Island boasts 20 locations with geothermal potential, with resources capable of generating up to 739.5 MWe. Notably, by 2023, three Geothermal Power Plants (PLTP) will be operational on Flores Island, including Ulumbu PLTP, Mataloko PLTP, and Sokoria PLTP. These developments have positioned Flores as the first island in Indonesia to surpass the Renewable Energy mix target of 25.38%.